2015
DOI: 10.14202/vetworld.2015.532-536
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide markers of D-loop for identification of Indian wild pig (Sus scrofa cristatus)

Abstract: Aim:Partial fragment of D-loop region extending from 35 to 770 were compared with corresponding sequences of 16 wild pigs and 9 domestic pig breeds from different parts of the world for detection of single nucleotide polymorphism (SNP) markers in the region. The paper also reappraises SNP markers from two fragments of cytochrome b gene and a fragment 12S rRNA gene distinguishing the Indian wild pig from other pig species of the world.Materials and Methods:Deoxyribonucleic acid (DNA) was isolated from 14 and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Literatures review and in silico analysis were performed to determine the primers used in this study: universal primer pair for PCR-RFLP [15] and two sets of primer pairs for duplex PCR [16,17]. Analysis of primer characteristics was summarized in table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literatures review and in silico analysis were performed to determine the primers used in this study: universal primer pair for PCR-RFLP [15] and two sets of primer pairs for duplex PCR [16,17]. Analysis of primer characteristics was summarized in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Duplex PCR was carried out using two porcine-specific primers [16,17] simultaneously. Annealing temperature was optimized to obtain the most effective amplification result.…”
Section: Primer Characterization Analysismentioning
confidence: 99%
“…The mtDNA contains a non-coding (D-loop) sequence comprising regulatory sequences regulating both replication and transcription of the mtDNA [ 8 ]. Many studies of farm animals, including pigs, have shown the effectiveness of applying the D-loop as a diversity marker when studying the mitochondrial genome [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The introgression of exotic genome under state sponsored programs to upgrade the local population using semen or live animals of exotic breeds has diluted the gene pool of local breeds, thus breed specification of the local domestic pig remains questionable. Most studies on Indian domestic pig mitochondrial DNA (MtDNA) are restricted to capillary electrophoresis (CE)-derived short sequence fragments analysis of cytocgrome b, 12S rRNA (Jadav et al 2014a,b), D-loop region of mitogenome (Srivastava et al 2014). There are no reports on characterization of the complete mitogenome of any of the domestic pigs of India.…”
mentioning
confidence: 99%
“…2014a , b ), D-loop region of mitogenome (Srivastava et al. 2014 ). There are no reports on characterization of the complete mitogenome of any of the domestic pigs of India.…”
mentioning
confidence: 99%